2006
DOI: 10.1007/s10278-006-0857-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Contribution of Virtual Endoscopy in Diseases of the Upper Airways

Abstract: Purpose: Virtual endoscopy (VE) is a new diagnostic tool that generates 3-dimensional (3D) views of a lumen by exploiting cross-sectional images. The purpose of this study was to evaluate the usefulness of VE as a diagnostic tool in the diseases of the larynx and pharynx. Materials and Methods: Twenty-two patients with a mean age of 57 years were included in the study. The patients underwent larynx examination, optical endoscopy (OE), and computed tomography (CT) of the larynx. Later, VE was produced from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Virtual laryngoscopy has previously described advantages in obtaining views from below an obstructing lesion and in delineating vocal cord lesions [21] and multiple stenoses such as those seen in Wegener granulomatosis [22]. Benign and malignant intraluminal masses in the head and neck region have also been shown to be accurately reproduced using virtual imaging [17,21,23], which is consistent with our findings and fundamental for its utility in planning an airway strategy. Virtual imaging uniquely offers a noninvasive, safe, and accurate method to map the upper airway for difficult airway management planning.…”
Section: Discussionsupporting
confidence: 88%
“…Virtual laryngoscopy has previously described advantages in obtaining views from below an obstructing lesion and in delineating vocal cord lesions [21] and multiple stenoses such as those seen in Wegener granulomatosis [22]. Benign and malignant intraluminal masses in the head and neck region have also been shown to be accurately reproduced using virtual imaging [17,21,23], which is consistent with our findings and fundamental for its utility in planning an airway strategy. Virtual imaging uniquely offers a noninvasive, safe, and accurate method to map the upper airway for difficult airway management planning.…”
Section: Discussionsupporting
confidence: 88%
“…In comparison to FFL, VE has been found to be particularly useful in cases of severe stenosis, which the conventional endoscope cannot pass through. 7 , 8 , 10 , 15 , 16 Besides, with the volumetric data and reconstructions, the area of stenosis can be viewed from different angulations and sides. 17 , 18 Furthermore, this modality can be used when the patient cannot tolerate FFL, allowing the assessment of the airway without the use of general anaesthesia and exposure to associated risks such as trauma to the teeth, the neck and the airway.…”
Section: Discussionmentioning
confidence: 99%
“…8 , 14 On the other hand, VE has multiple limitations described by several studies, including radiation exposure and the inability to identify mucosal irregularities or flat lesions. 7 , 8 , 16 , 19 Moreover, this technique cannot give real-time imaging, 16 whereas in endoscopy, the visualisation of the airway mucosa allows the evaluation of the intraluminal anatomy, the morphology, vascularisation and colour of the mucosa, 12 giving the opportunity to recognise abnormalities and take tissue samples. 8 , 10 Additionally, the quality of the images depends on the collaboration of the patient, 10 and it requires specialised software and time to do the reconstructions, thereby increasing the costs, 11 although with technology improvement, the reconstructions are quicker and with better detail.…”
Section: Discussionmentioning
confidence: 99%
“…This has been shown previously by the broad applicability of VE as a diagnostic tool in a number of medical specialties, such as radiology and thoracic surgery, for lesions in the head and neck, trachea, and bronchial tree. [23][24][25][26][27][28][29][30][31][32] Nørskov et al found that, in almost half of the patients with anticipated difficult tracheal intubation, the anesthesiologist planned to attempt direct laryngoscopy for intubation, even when difficult intubation and difficult face mask ventilation were anticipated. 7 We have shown that there was a change in the airway management plan in half of the cases when VE videos were reviewed, with the vast majority changing to a more cautious plan (90.6%).…”
Section: Discussionmentioning
confidence: 99%